Most prevalent jobs of young bachelor’s degree graduates by detailed field of study - Marc Frenette; Tomasz Handler (Economic and Social Reports)
Investing in a postsecondary education is one of the most important decisions made by people over their lifetime. Understanding the potential outcomes associated with specific postsecondary academic programs may help inform young people, but most of the available information focuses on earnings. While important, earnings say little about what postsecondary graduates are likely to do in their career, which may factor heavily in their decision-making process. This article presents the most prevalent jobs held by graduates of Canadian bachelor’s degree programs aged 25 to 34 using the 2021 Census of Population.